Mekanisme Penerbitan Sertifikat Keselamatan Kapal TB Cavalo Marinho 09 di KSOP Khusus Batam oleh PT. Surya Samudera Indah Batam - Dinda Safitri; Syarifur Ridho; Taruna Ginting (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Maritime safety is a crucial aspect of sea transportation regulated by Law No. 17 of 2008, which mandates the fulfillment of ship seaworthiness and crew requirements. To ensure these standards are met, the Directorate General of Sea Transportation carries out continuous supervision through the issuance of the Ship Safety Certificate. This certificate ensures that the ship meets the material, construction, machinery, stability, and equipment requirements in accordance with regulations, including the SOLAS International Convention. To enhance efficiency, the SIMKAPEL digital system was developed to accelerate the certification process online. This study aims to analyze the mechanism of issuing the Ship Safety Certificate for the TB. Cavalo Marinho 09, managed by PT. Surya Samudera Indah Batam at the Batam Special Port Authority (KSOP). The method used is a combination of field and library research, with direct observation and active participation for six months. The results indicate that the certification process at KSOP Batam is in accordance with the applicable Standard Operating Procedures (SOP) and supported by the SIMKAPEL system. The study concludes that compliance with regulations and the utilization of digital systems are essential for maritime safety and efficiency.